2012
DOI: 10.1128/aac.05680-11
|View full text |Cite
|
Sign up to set email alerts
|

An Organoselenium Compound Inhibits Staphylococcus aureus Biofilms on Hemodialysis Catheters In Vivo

Abstract: Colonization of central venous catheters (CVCs) by pathogenic bacteria leads to catheter-related bloodstream infections (CRBSIs). These colonizing bacteria form highly antibiotic-resistant biofilms. Staphylococcus aureus is one of the most frequently isolated pathogens in CRBSIs. Impregnating CVC surfaces with antimicrobial agents has various degrees of effectiveness in reducing the incidence of CRBSIs. We recently showed that organoselenium covalently attached to disks as an antibiofilm agent inhibited the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 39 publications
0
51
0
5
Order By: Relevance
“…2b). Quantitative analysis of the biofilm using the COMSTAT program revealed a biomass (35.35 mm 3 per mm 2 ), mean thickness (120.79 mm) and surface area (2.15610 7 mm 2 ) similar to P. aeruginosa biofilms in the flow-through continuous-culture system (Schaber et al, 2007) and S. aureus AH133 biofilms on haemodialysis catheters in vivo (Tran et al, 2012). Quantification of the bacteria present showed a 4-5 log increase in the number of micro-organisms from 10 3 -10 4 c.f.u.…”
Section: Garo Inhibits Biofilm Development By Grampositive Wound Pathmentioning
confidence: 99%
“…2b). Quantitative analysis of the biofilm using the COMSTAT program revealed a biomass (35.35 mm 3 per mm 2 ), mean thickness (120.79 mm) and surface area (2.15610 7 mm 2 ) similar to P. aeruginosa biofilms in the flow-through continuous-culture system (Schaber et al, 2007) and S. aureus AH133 biofilms on haemodialysis catheters in vivo (Tran et al, 2012). Quantification of the bacteria present showed a 4-5 log increase in the number of micro-organisms from 10 3 -10 4 c.f.u.…”
Section: Garo Inhibits Biofilm Development By Grampositive Wound Pathmentioning
confidence: 99%
“…We examined the ability of S. salivarius and S. mutans to form biofilms on selenium-free dental sealant discs, using the modified microtiter biofilm assay (Hammond et al, 2010;Tran et al, 2012). We recovered an average of 4 x 104 CFU/sealant disc for S. salivarius and an average of 2 x 105 CFU/sealant disc for S. mutans, using as control a selenium-free sealant (Figs.…”
Section: Organo-selenium Dental Sealants Inhibit the Development Of Smentioning
confidence: 99%
“…The biofilm assay was performed, as previously described, by a modified microtiter plate assay (Hammond et al, 2010;Tran et al, 2012). Seven-millimeter discs of selenium-free dental sealant or organo-selenium dental sealants were incubated in 1 mL BHI media in the presence of approximately 1,000 initial colony-forming units (CFU) of S. salivarius or 7,500 CFU of S. mutans in each well of the microtiter plate.…”
Section: Dental Sealant Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because animal studies have not yet been reported for these approaches, the in vivo efficacy of such antibiofilm techniques remains unclear. One possible exception is the recent report by Tran et al (18). These investigators coated hemodialysis catheters with an organoselenium compound through a wet coating process consisting of multiple steps and taking 3 days to complete; the organose-lenium-coated catheters inhibited S. aureus biofilms both in vitro and in vivo.…”
mentioning
confidence: 92%